Unveiling the synergistic effect of an nZVI–SiO2–TiO2 nanocomposite for the remediation of dye contaminated wastewater† - Murtala, Namakka; Md Rezaur, Rahman; Khairul Anwar, Mohamad Said; Kuok, King Kuok; Fahmi Asyadi, Md Yusof; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman (The Royal Society of Chemistry, 2024)
Water contamination and scarcity pose critical global challenges. Existing water remediation technologies such as membrane technologies lack hydrophilic surface properties, prompting the need for novel, highly efficient supportive materials. Photocatalysis emerges as a promising solution for degrading organic pollutants in wastewater. However, existing photocatalysts such as titanium dioxide (TiO2) suffer from rapid recombination of photogenerated charge carriers and lower catalytic activity, hindering performance. Herein, a novel, high sorption capacity nZVI–SiO2–TiO2 nanocomposite material was synthesized via a combined chemical reduction approach. The influence of synthesis pH and the synergistic effects of nZVI, SiO2, and TiO2 on the physicochemical properties and overall performance of the nZVI–SiO2–TiO2 nanocomposite were investigated. Three sets of nZVI–SiO2–TiO2 nanocomposites were synthesized by varying synthesis pH from 2 to 4. MB dye degradation experiments and thermal analysis revealed that the nZVI– SiO2–TiO2 nanocomposite synthesized under pH 2 synthesis conditions exhibited the fastest dye degradation rate, highest removal efficiency (100%), and thermal stability. Characterization techniques, including FTIR, EDS (energy dispersive X-ray spectroscopy), SEM, BET (Brunauer–Emmett–Teller), XRD, TGA (thermogravimetric analysis), and DSC (differential scanning calorimetry), revealed that lower nZVI–SiO2–TiO2 synthesis pH enhanced the material’s specific surface area, crystallinity, and the interfacial interactions of nZVI, SiO2, and TiO2 components in the nanocomposite. The reusability test showed 490% efficiency after 5 successive cycles. The sorption mechanism and methylene blue (MB) dye speciation test corroborated the synergistic adsorption and reduction potential of nZVI–SiO2–TiO2 functional materials with 100% mineralized methylene blue (MB+ species) at MB dye solution pH above 6.0. After economic considerations, it is believed that the exceptional adsorption and recycling abilities of the novel nZVI–SiO2–TiO2 material, coupled with its thermal stability, could counterbalance its upfront expenses, potentially making it a feasible choice for wastewater treatment applications.